Pharmacological approach to smoking cessation and effective intervention models - Alzahrani, Hadeel H.; Alasmari, Yasir M.; Almutairi, Najwa A.; Aldajani, Shikhah G.; Alanazi, Faisal O.; Alsadiq, Amal A.; Alanazi, Eman J.; Abu Moailo, Hakeemah A.; Alotaibi, Jalawi T.; Alsubhi, Ammar M.; Bagais, Abdulrahman H.; Asfour, Ghassan M. (International Journal Of Community Medicine And Public Health, 2022)
One of the main public health issues is tobacco use, which is also associated with considerate morbidity and mortality worldwide. Smoking cessation lowers mortality and risk of future cardiovascular events. Smoking is a true chronic condition that is defined by the emergence of a dependency state that is primarily caused by nicotine. Smokers are typically unable to quit smoking on their own. There are numerous approaches to treating smoking addiction, including both non-pharmacological such as behavioural counselling and pharmacological therapy. The effectiveness and safety of smoking cessation medications in everyday life are currently widely acknowledged. The primary pharmacological methods for quitting smoking include nicotine replacement therapy, varenicline, bupropion, and cytisine. Even in patients with chronic cardiovascular disease, their effectiveness and safety have been demonstrated. It has been demonstrated that nicotine replacement therapy, bupropion, varenicline, and cytisine increase the likelihood of cessation. Both varenicline and nicotine replacement therapy in combination are powerful tools for cessation. The likelihood of quitting is likewise increased by nortriptyline. Research suggests that none of the treatments seem to have a frequency of adverse reactions that would limit their usage. The clinician should tailor the smoking cessation strategy based on the most recent scientific data and the patient's preferences, giving particular attention to those patients who have certain cardiovascular and psychiatric comorbidities. The purpose of this research is to review the available information about pharmacological approach to smoking cessation and effective intervention models.